The Vertical Profile of Dissolved oxygen on the Bakuok Lake in Aursati Village Tambang Subdistrict Kampar District Riau Province - Hidayati Hasibuan; Asmika H. Simarmata; Clemens Sihotang (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research has been done on the Bakuok Lake in Aursati Village Tambang Subdistrict District Kampar in March - April 2014. This research aims to understand the vertical profile of dissolved oxygen in this reservoir. The research used survey method. The sample’s were taken from three station and vertically in three sampling point. The parameters of water quality measured were pH, phosphate, nitrate, dissolved oxygen, free carbon dioxide, brightness, temperature and depth. Sampling vertical based on transparency, namely at surface, 11/2 Secchi depth and in the bottom of lake. The result shown the concentration of dissolved oxygen at the surface: 3,55 mg/L – 5,33 mg/L; in the 11/2 Secchi depth; 2,32 mg/L – 3,75 mg/L; and the bottom of lake: 1,78 mg/L – 2,74 mg/L. The vertical profile of dissolved oxygen showed the concentration increased with the increment of depth. The water quality parameter analyzed were temperature: 29,6oC – 30oC; transparancy 74,3 cm – 93,7 cm; depth: 208 cm – 332 cm; pH: 6, free karbon dioxide: 4,66 mg/L- 15,31 mg/L, nitrate ; 0.01 mg/L – 0.12 mg/L, phosphate: 0.01 mg/L – 0.17 mg/L and phytoplankton ranged from 20.415 sel/L – 39,509 sel/L. The concentration of dissolved oxygen in Bakuok Lake showed the highest decrement, in a general the parts quality still support the aquatic organism life.Keywords: Dissolved oxygen, the vertical profiles, Bakuok Lake